Peran Buku Cerita Bergambar Digital dalam Meningkatkan Literasi pada Anak Usia Dini - Irika Widiasanti; Annisa Ayu Yuslina; Dwi Seftiani Syafitri; Fazla Mawla Yumadia; Gita Rianing Tiyas; Puja Istiqoma (Badan Penerbit STIEPARI Press, 2025)
This study discusses the role of digital picture story books in improving literacy in early childhood. Literacy in early childhood does not only include reading and writing skills, but also understanding, interpretation, and communication with the surrounding environment. The method used in this study is the library method by searching, collecting, and analyzing information found in scientific articles and other sources. The research subjects came from relevant literature sources that discuss the development of early childhood literacy through digital media, one of which is the research of López-Escribano et al. The object of this study is the role or influence of picture story books in improving literacy in early childhood. The data analysis technique in this study uses content analysis, which is a technique by identifying or analyzing the meaning of the contents of various written sources that are studied that are relevant to the research topic. The results of the study through understanding the characteristics of the kingdom show an increase in literacy skills and the effectiveness of using picture story books in early childhood.